Economics of healthcare financing in WHO South East Asia Region - Majumder, Md Anwarul Azim (South East Asia Journal of Public Health, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/seajph.v2i2.15936 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 3-4